Analisis Faktor Pengetahuan Dengan Upaya Pencegahan Dermatitis Pada Nelayan Di Desa Tulehu - Ira Sandi Tunny (Lembaga Pengembangan Kinerja Dosen, 2022)
Background: Fishermen in Tulehu Village, Salahutu District have a good level of knowledge and have better prevention efforts against dermatitis compared to fishermen who have sufficient level of knowledge. This can be interpreted that knowledge is a very important domain for the formation of one's actions because with high knowledge can create good behavior.Objective:To analyze the Knowledge Factor with Dermatitis Prevention Efforts in Fishermen in Tulehu Village. Research Method: This research is an analytic descriptive study with a cross sectional approach. Sampling technique usingPurposive Sampling. The sample in this study were 95 respondents who live in the village of Tulehu. The results of the study: The results of the study obtained that there is a relationship between knowledge and efforts to prevent dermatitis in fishermen in Tulehu Village, Salahutu District, with a value of p = 0.000. Conclusions and suggestions: It is recommended to be able to maintain personal hygiene and use complete PPE while working, and increase knowledge and efforts to prevent dermatitis.